VirtualPREX: Providing virtual professional experience for pre-service teachers - Masters, Y.; Gregory, S.; Dalgarno, B.; Reiners, Torsten; Knox, V. (Nova Science Publishers, 2015)
Professional experience (or practicum) is problematic within teacher education courses because preparation for, and the quality of , placements can be inconsistent. Pre-service teachers can commence their first placement without some of the requisite skills and off-campus pre-service teachers do not always have opportunities to practise any skills at all pre-placement. VirtualPREX is an innovative approach to professional experience preparation, providing opportunities for practice in a virtual world such as Second Life. In the chapter the authors outline the rationale for this innovation and then report on the data from the pilot trials of the VirtualPREX role plays where pre-service teachers role-played the teacher and students in a Second Life virtual classroom. The chapter concludes with a discussion of the next steps in the project.